Pengaruh Brand Image Dan Brand Awareness Terhadap Keputusan Pembelian Di Market Place Tokopedia Pada Produk Skincare Kahf Di Kalangan Gen Z - Saputra, Aditdya Bagus; Savitri, Citra; Faddila, Syifa Pramudita (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Adults The importance of taking care of oneself in this modern era has increased, as a lack of skin and facial care can lead to a dull appearance and the appearance of signs of aging quickly. One of the rising trends in recent years is men's grooming or commonly known as Men's Grooming. PT. Paragon Technology, a skincare company in Indonesia, has launched its newest brand in 2020 called Kahf. Kahf is a skin care product for men that offers innovation according to men's needs and can solve skin problems according to different skin types. This study aims to examine the relationship between brand image and brand awareness on online purchasing decisions for Kahf products on the Tokopedia platform. Quantitative method with Partial Least Square - Structural Equation Model (PLS-SEM) approach. The population of this study were Management Students at Buana Perjuangan Karawang University class of 2019-2022 who are men from generation Z and have used Kahf products. A total of 132 respondents met these criteria, however, a sample of 100 students was taken. Data was collected by filling out a questionnaire, and data analysis was carried out using the SmartPLS 3.0 application. The results of the study found that the brand image variable had a negative and insignificant effect on the purchase decision variable. Meanwhile, the brand awareness variable has a positive and significant effect on purchasing decisions.